A Statutory Analysis of State-Level Sex Offender Residency, Loitering, Presence, and Entry Restrictions. (February 2023) - Navarro, John C.; Knudsen, Kate E.; Richardson, Christina L.
Residency restrictions stipulate the living arrangements of sex offenders, but underdiscussed are geographic restrictions that limit spatial interactions relating to loitering, presence, and entry. Our statutory analysis of state-level geographic restrictions identifies 38, 18, 19, and 14 states which have implemented residency, loitering, presence, and entry restrictions. Geographic restrictions are widely adopted, particularly between 2006 and 2010, and are dispersed randomly by region and division, with some states being more comprehensive than others, particularly in West South Central. Residency restrictions were typically older and longer, with distance markers progressively less common for loitering, presence, and entry restrictions. Geographic restrictions were more often offense-specific than registration-specific and demonstrated heterogeneity in the number and types of prohibited venues that were commonly youth-centric.